Performance analysis of differential phase modulation for HF communication - Mohd. Saad, Nohashimah (2004)
Data transmission using HF spectrum (3-30 MHz) is widely used due to its ability in providing long distance communications at low cost. Due to multipath fading problems in HF channels, the maximum symbol rate of data transmission is limited to 100 baud per second. Differential multiple phase modulation techniques can be used to increase the transmission rate without changing the baud rate. Advanced digital modulation techniques based on PSK is used due to its reliability in providing lower error rate compared to other modulation techniques, such as modulation based on FSK. Unlike coherent detection, phase synchronization is not critical for the differential detection, and implementation can be made simpler in differential multiple phase modulations. For this study, the BER and PER performance of DPSK, DQPSK, D8PSK and D16PSK modulation techniques are presented. The performance evaluation for each modulation are investigated in additive white Gaussian noise environment and random phase delay is included that is based on uniform distribution. In general, the BER and PER performance for differential multiple phase detection decrease for every doubling of phases, but the main advantage is the reliability in data transmission in achieving higher transmission rate